2017
DOI: 10.1111/cup.13043
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum levels and cutaneous expression of lipoprotein (a) in 38 patients with livedoid vasculopathy

Abstract: Increased Lp(a) expression in lesional skin of LV patients suggests the role of Lp(a) in the thrombo-occlusive vasculopathy observed in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…Both facts are similar to data published by Renner et al . while others had described a female‐to‐male ratio of 3 : 1 and a clearly younger population with a mean age of 32 or 37 years . The average BMI in our study population was only slightly lower (25.6 kg/m²) compared to an age‐matched German population with a BMI of 26.4 kg/m² although BMI was elevated in 40% of LV patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both facts are similar to data published by Renner et al . while others had described a female‐to‐male ratio of 3 : 1 and a clearly younger population with a mean age of 32 or 37 years . The average BMI in our study population was only slightly lower (25.6 kg/m²) compared to an age‐matched German population with a BMI of 26.4 kg/m² although BMI was elevated in 40% of LV patients.…”
Section: Discussionsupporting
confidence: 91%
“…Both facts are similar to data published by Renner et al 15 while others had described a female-to-male ratio of 3 : 1 16,17 and a clearly younger population with a mean age of 32 or 37 years. 18,19 The average BMI in our study population was only slightly lower (25.6 kg/m²) compared to an age-matched German population with a BMI of 26.4 kg/m² 20 although BMI was elevated in 40% of LV patients. In addition, the rate of hypertension (70%) was clearly higher in LV patients compared to the prevalence of hypertension in females (44%) or males (51%) in Germany at the same age.…”
Section: Discussionmentioning
confidence: 52%
“…Lipoprotein A (LpA) plays a major role in thrombo-occlusive vasculopathy. 58,59 Criado et al demonstrated thrombosis, fibrin, and LpA deposition on cutaneous blood vessels in a patient with livedoid vasculopathy. Convincing data has shown genetic variability in LpA levels between ethnic populations.…”
Section: Capsule Summary Dmentioning
confidence: 99%
“…Alterations in plasma lipoprotein(a) level have been associated with the pathogenesis of vasculopathies such as livedoid vasculopathy and vasculitis associated with Behcet's disease. [23][24][25] Studies with a larger number of patients are required to establish whether lipoprotein(a) has a thrombotic role in the pathogenesis of CPAN.…”
Section: Discussionmentioning
confidence: 99%